Photodynamic therapy of human colorectal carcinoma cell line - Stukavec, Jan; Duchac, Vitezslav; Horak, Ladislav; Pouckova, Pavla (Photomedicine and laser surgery, 2009)
Colorectal cancer is one of the most common cancers in Europe and North America and it is the most common gastrointestinal carcinoma. The population in the Czech Republic has a higher incidence of colorectal carcinoma compared to other countries. Efforts are underway to develop better screening strategies and novel therapies to improve patient survival rates. Despite all efforts, colorectal cancer remains one of the leading causes of death from cancer. Photodynamic therapy (PDT) is an established modality for the treatment of various diseases. The PDT procedure involves the administration of a photosensitizer followed by illumination. The anti-tumor effects result from direct killing of malignant cells, shutting down of the tumor's vasculature, and the promotion of an immune response. In our experiment, we examined the effects of phototherapy with disulfonated hydroxyaluminum phthalocyanine (Al(OH)S2Pc) on the growth of colorectal carcinoma cells, in an effort to offer a new treatment modality for patients with this disease.
Keywords: fotosenzibilizující látky; myši; nádorové buněčné linie; Colorectal Neoplasms; Mice, Nude; Photosensitizing Agents; zvířata; fotochemoterapie; Humans; Cell Line, Tumor; Mice; transplantace nádorů; kolorektální nádory; Photochemotherapy; myši nahé; Neoplasm Transplantation; lidé; Animals